Breaking barriers: the story of a dalit chief secretary - Rao, Kaki Madhava; Sankaran, S. R. (Hyderabad EMESCO Books, 2022)
The book contains an inspiring story of how a son of a Dalit Landless Labourer went on to reach the highest post of a Chief Secretary by breaking all the barriers. It is a story of how one can overcome the struggles in the form of poverty, caste, creed, religion, politics and reach the most enviable position.
Keywords: Story Chief Secretary -- IAS as an author